2015
DOI: 10.1186/s12936-015-0621-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving uptake and use of malaria rapid diagnostic tests in the context of artemisinin drug resistance containment in eastern Myanmar: an evaluation of incentive schemes among informal private healthcare providers

Abstract: BackgroundAs efforts to contain artemisinin resistance and eliminate Plasmodium falciparum intensify, the accurate diagnosis and prompt effective treatment of malaria are increasingly needed in Myanmar and the Greater Mekong Sub-region (GMS). Rapid diagnostic tests (RDTs) have been shown to be safe, feasible, and effective at promoting appropriate treatment for suspected malaria, which are of particular importance to drug resistance containment. The informal private sector is often the first point of care for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 32 publications
(23 reference statements)
1
30
2
Order By: Relevance
“…After this study took place, the two interventions suggested above were indeed carried out, to successfully replace oral artemisinin-based monotherapies with subsidized QA-ACT [ 8 ], and then to ensure their proper use through the use of subsidized RDTs [ 14 16 ]. Interestingly, educational campaigns to both the provider and the community proved to be effective, with increased educational visits to providers leading to increased levels of RDT use [ 14 16 ]. This follow-up intervention also offered the potential to crowd out the supply of sub-standard and counterfeit ACT, offering a relatively simple solution to an otherwise challenging problem [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…After this study took place, the two interventions suggested above were indeed carried out, to successfully replace oral artemisinin-based monotherapies with subsidized QA-ACT [ 8 ], and then to ensure their proper use through the use of subsidized RDTs [ 14 16 ]. Interestingly, educational campaigns to both the provider and the community proved to be effective, with increased educational visits to providers leading to increased levels of RDT use [ 14 16 ]. This follow-up intervention also offered the potential to crowd out the supply of sub-standard and counterfeit ACT, offering a relatively simple solution to an otherwise challenging problem [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myanmar has the greatest malaria incidence in the Greater Mekong Region [ 1 , 8 ] and its new government and poorly resourced public health system will have to overcome a variety of political, economic and logistic challenges if malaria is to be eliminated [ 9 ]. Several interventions have already been implemented and these include the training and deployment of community health workers [ 10 , 11 ], the provision of insecticide-treated bed nets [ 12 ] and strategies to improve access to rapid diagnostic tests [ 13 ] and artemisinin-based combination therapy (ACT) [ 14 ]. There has also been a concerted effort to improve diagnosis and management of the disease in the private sector where the majority of malaria cases are managed [ 15 ]; here there has been a particular focus on the removal of poor quality ACT and artesunate monotherapy [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hrp2 gene, however, is dispensable, and parasite strains that have deleted this gene and escape RDT detection are on the rise. In a recent modeling study, false-negative rates with HRP2-based tests were predicted to attain 20% in many parts of Africa by 2030 [80]. Nucleic acid amplification tests (NAAT) are superior for detecting mixed infections, cases with low parasitemia.…”
Section: Plasmodium and Anophelines Interplay In Response To The Intementioning
confidence: 99%